Differential expression of mouse neural cell-adhesion molecule (N-CAM) mRNA species during brain development and in neural cell lines - Gennarini, G (J Neurosci, 1986)
The cell-adhesion molecules N-CAM (neural cell-adhesion molecule) are ligands in the formation of cell-cell bonds and have been shown to play important roles during neuro-ontogenesis. They exist in several molecular forms which differ at the protein and carbohydrate levels. The regulation of the expression of these different forms is an important issue that bears on such questions as to how adhesive interactions between cells are modulated during morphogenesis. In the present study we have used N-CAM cDNA clones to investigate the expression of the cognate mRNAs in the mouse and rat brain and in 2 neural cell lines. The results were compared with the levels of the different N-CAM proteins. We made the following observations. A complex set of 5 size classes of mRNAs--which show developmental, regional, and cell-type-dependent variations in their expression--hybridize to 1 of our cDNA probes. While embryonic brain contains N-CAM gene transcripts 7.4, 6.7, and 4.3 kilobases (kb) in length, 2 additional mRNAs of 5.2 and 2.9 kb appear postnatally. Transformed brain cells of an astrocytic character express predominantly mRNAs of 6.7, 4.3, and 2.9 kb and a neuroblastoma line those of 7.4, 6.7, 4.3, and 2.9 kb. There are important quantitative changes in the amount of N-CAM message expressed during brain development, with a peak around birth, suggesting that N- CAM synthesis is controlled at the transcriptional level. A comparison of N-CAM protein and mRNA levels reveals a striking correlation between the relative concentrations of the Mr 120,000 N-CAM protein (N-CAM120) and the 5.2 kb transcript.(ABSTRACT TRUNCATED AT 250 WORDS)